2018
DOI: 10.1016/j.jogn.2018.04.134
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Informed Consent to Facilitate Recruitment of Pregnant Women Into Research

Abstract: Methods to obtain informed consent digitally or electronically may increase the participation of racially and geographically diverse pregnant women in prospective research, which is essential to improve the evidence base for maternity care. We evaluated the feasibility and utility of e-consent in the first year of a multiyear clinical trial involving pregnant women. Of the 86 women screened, 71 were eligible, 65 (93% of eligible) agreed to review the e-consent form, and 61 (86% of eligible) completed the e-con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
(15 reference statements)
1
25
0
Order By: Relevance
“…Study characteristics are summarised in Table 3 . There were 6 cohort studies, [ [39] , [40] , [41] , [42] , [43] , [44] ] 5 qualitative studies [ [45] , [46] , [47] , [48] , [49] ], 4 RCTs [ [50] , [51] , [52] , [53] ], 2 mixed-methods studies [ 54 , 55 ] and 1 case-control study [ 56 ] included in this review. With the exception of 2 studies conducted in the UK [ 45 , 54 ], all other studies were undertaken in the USA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study characteristics are summarised in Table 3 . There were 6 cohort studies, [ [39] , [40] , [41] , [42] , [43] , [44] ] 5 qualitative studies [ [45] , [46] , [47] , [48] , [49] ], 4 RCTs [ [50] , [51] , [52] , [53] ], 2 mixed-methods studies [ 54 , 55 ] and 1 case-control study [ 56 ] included in this review. With the exception of 2 studies conducted in the UK [ 45 , 54 ], all other studies were undertaken in the USA.…”
Section: Resultsmentioning
confidence: 99%
“…The demographics of study participants were generally representative of their local population, although many authors noted a predominance of educated, white females [ 39 , 40 , 44 , 45 , 47 , 50 , 51 , 53 , 55 ]. Five studies targeted a specific population; pregnant women [ 42 ], participants from urban and rural communities [ 48 ], participants under-represented in research in the United States [ 49 ], older adults (65 years or older) [ 55 ] and legal authorised representatives consenting by proxy for medical research [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early results using remote eConsent with the Vanderbilt STRIDE exemplar study suggest that utilization of eConsent may increase the participation of minority pregnant women in prospective research. Researchers concluded that eConsent was effective for consenting women with low health literacy [34]. Further work over the course of the STRIDE project and more detailed data capture of participant interactions with the eConsent framework will assess the impact of the framework on recruitment and retention of minority participants in research studies and help to inform best practices for utilizing the framework in remote consenting.…”
Section: Remote Consenting and Telemedicinementioning
confidence: 99%